Problematika Terhadap Bazar Jual Beli Pakaian Bekas Thrifting Di Surakarta - Ayu Widya Wardani; Suraji Suraji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research describes and examines the issues arising from the secondhand clothing bazaar (thrifting) in Surakarta. The prohibition of thrifting in Indonesia is stipulated in Law Number 7 of 2014 concerning Trade in Article 47 paragraph (1). Despite the existing prohibition, the fact remains that thrifting activities are still widespread in Indonesia, attracting the interest of event organizers to host large-scale thrifting-themed events, thus leading to an increase in both traders and event organizers involved in thrifting activities in Indonesia. This study is an empirical legal research of a descriptive nature. The types and sources of research data include primary and secondary data as well as primary, secondary, and tertiary legal materials. Data collection techniques employed include interviews, followed by qualitative data analysis methods. The research findings indicate several problems with the secondhand clothing bazaar in Surakarta, including the potential decline in public interest towards local products, with a shift towards purchasing secondhand clothing. Furthermore, secondhand clothing may potentially harbor diseases such as mold, as evidenced by tests conducted by the Ministry of Trade. The influx of imported secondhand clothing also generates textile waste, and the efforts by the Indonesian government to halt the secondhand clothing trade have not been fully effective.